Transform-Us! cluster RCT: 18-month and 30-month effects on children's physical activity, sedentary time and cardiometabolic risk markers. (25th November 2022) - Salmon, Jo; Arundell, Lauren; Cerin, Ester; Ridgers, Nicola Dawn; Hesketh, Kylie D; Daly, Robin M; Dunstan, David; Brown, Helen; Della Gatta, Jacqui; Della Gatta, Paul; Chinapaw, Mai J M; Shepphard, Lauren; et al.
Abstract : Objective: To test the efficacy of the Transform-Us! school- and home-based intervention on children's physical activity (PA), sedentary behaviour (SB) and cardiometabolic risk factor profiles. Methods: A 30-month 2×2 factorial design cluster randomised controlled trial delivered in 20 primary schools (148 Year 3 classes) in Melbourne, Australia (2010–2012), that used pedagogical and environmental strategies to reduce and break up SB, promote PA or a combined approach, compared with usual practice. Primary outcomes (accelerometry data; n=348) were assessed at baseline, 18 and 30 months. Secondary outcomes included body mass index (BMI) and waist circumference (WC) (n=564), blood pressure (BP) (n=537) and biomarkers (minimum n=206). Generalised linear mixed models estimated the interactive effects of the PA and SB interventions on the outcomes. If there was no interaction, the main effects were assessed. Results: At 18 months, there were intervention effects on children's weekday SB (−27 min, 95% CI: −47.3 to −5.3) for the PA intervention, and on children's average day PA (5.5 min, 95% CI: 0.1 to 10.8) for the SB intervention. At 30 months, there was an intervention effect for children's average day SB (−33.3 min, 95% CI: −50.6 and −16.0) for the SB intervention. Children's BMI (PA and SB groups) and systolic BP (combined group) were lower, and diastolic BP (PA group) was higher. There were positive effects on WC at both time points (SB intervention) and mixed effects on blood parameters. Conclusions: The Transform-Us! PA and SB interventions show promise as a pragmatic approach for reducing children's SB and adiposity indicators; but achieving substantial increases in PA remains challenging. Trial registration: ISRCTN83725066 ; ACTRN12609000715279.